2008
DOI: 10.1002/pmh.48
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence, alexithymia and borderline personality disorder traits in young adults

Abstract: Background A relationship between emotional intelligence (EI) and borderline personality disorder (BPD) has recently been identifi ed. EI has also been found to overlap considerably with alexithymia, a construct associated with emotion processing and emotion regulation. EI and alexithymia may further our understanding of the relationship between emotion processing, emotion regulation and BPD. Aims We examined the relationships between EI, alexithymia and BPD traits, hypothesizing that EI and alexithymia woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 30 publications
4
13
0
Order By: Relevance
“…For example, they display poorer reflective functioning on the Adult Attachment Interview (Fischer‐Kern, Buchheim, Hörz et al ., ; Fonagy, Leigh, Steele et al ., ; Levy, Meehan, Kelly et al ., ). Studies also show that patients with BPD have disturbed identity (Jørgensen, ; Jørgensen, Berntsen, Bech, Kjølbye, Bennedsen & Ramsgaard, ; Wilkinson‐Ryan & Westen, ) and high alexithymia, which refers to difficulties recognizing and describing personal emotional states (Domes, Grabe, Czieschnek, Heinrichs & Herpertz, ; Joyce, Fujiwara, Cristall, Ruddy & Ogrodniczuk, ; Webb & McMurran, ; Zlotnick, Mattia & Zimmerman, ). Other studies show that BPD is associated with lower empathy (Davis, ; Dziobek, Preißler, Grozdanovic, Heuser, Heekeren & Roepke, ; Eisenberg, Fabes, Murphy et al ., ; Harari, Shamay‐Tsoory, Ravid & Levkovitz, ; Jeung & Herpertz, ; New, Rot, Ripoll et al ., ; Ritter, Dziobek, Preißler et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, they display poorer reflective functioning on the Adult Attachment Interview (Fischer‐Kern, Buchheim, Hörz et al ., ; Fonagy, Leigh, Steele et al ., ; Levy, Meehan, Kelly et al ., ). Studies also show that patients with BPD have disturbed identity (Jørgensen, ; Jørgensen, Berntsen, Bech, Kjølbye, Bennedsen & Ramsgaard, ; Wilkinson‐Ryan & Westen, ) and high alexithymia, which refers to difficulties recognizing and describing personal emotional states (Domes, Grabe, Czieschnek, Heinrichs & Herpertz, ; Joyce, Fujiwara, Cristall, Ruddy & Ogrodniczuk, ; Webb & McMurran, ; Zlotnick, Mattia & Zimmerman, ). Other studies show that BPD is associated with lower empathy (Davis, ; Dziobek, Preißler, Grozdanovic, Heuser, Heekeren & Roepke, ; Eisenberg, Fabes, Murphy et al ., ; Harari, Shamay‐Tsoory, Ravid & Levkovitz, ; Jeung & Herpertz, ; New, Rot, Ripoll et al ., ; Ritter, Dziobek, Preißler et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…as greater risk for adverse mental health outcomes that span mood, anxiety, personality, and other psychiatric disorders (Saarijarvi, Salminen, & Toikka, 2006;Simeon, Giesbrecht, Knutelska, Smith, & Smith, 2009;Speranza, Loas, Wallier, & Corcos, 2007;Webb & McMurran, 2008). In particular, alexithymia has been consistently linked to posttraumatic stress disorder (PTSD), as emotional inhibition is a core feature of PTSD (Evren, Dalbudak, Cetin, Durkaya, & Evren, 2010;Spitzer, Vogel, Barnow, Freyberger, & Joergen Grabe, 2007).…”
mentioning
confidence: 99%
“…The latter ability is more closely related to emotional clarity than to attention to emotions, supporting the idea that alexithymia and emotional intelligence are independent constructs (Aradilla-Herrero, Tomás-Sábado, & Gómez-Benito, 2014). This conclusion is reinforced by studies that have examined the explanatory power of alexithymia and emotional intelligence and which have found that not only do these two constructs contribute to the explanation of different variables but also that they themselves are explained by different variables (Baughman, Schermer, Veselka, Harris, & Vernon, 2013;Grieve & Mahar, 2010;Webb & McMurran, 2008). In the only study found that analyzes the combined explanatory power of emotional intelligence and alexithymia over stress in undergraduates, it was found that emotional intelligence explains stress better than alexithymia (Mikolajczak, Luminet, & Menil, 2006).…”
Section: Burnout and Emotional Intelligencementioning
confidence: 97%